Penggunaan Majas dan Diksi dalam Lirik Lagu Sorai Karya Nadin Amizah - Nia Maulida (Universitas Palangka Raya, 2025)
Songs are included in oral Satra and are one of the oral traditions that are still popular today and are growing rapidly, giving birth to new musicians. Nadin Amizah’s song Sorai is one of the songs known for its compelling lyrics. This encourages researchers to examine the use of language styles or majas and word choice in the composition of the song. The author uses descriptive qualitative research and a stylistic approach to examine the lyrics of Nadin Amizah’s song Sorai. Words, phrases, and sentences in the song lyrics were included in the data collected. The research revealed the existence of 31 types of language styles and 41 forms of diction used in the song.